2018
DOI: 10.3390/molecules23010139
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Purification of Polyphenols from Aronia melanocarpa (Chokeberry) with Cellular Antioxidant and Antiproliferative Activity

Abstract: The aim of this study was the purification process of polyphenols from Aronia melanocarpa (chokeberry), and the purification parameters were optimised by adsorption and desorption tests. By comparing adsorption and desorption ability of polyphenols from chokeberry on six kinds of macroporous resin, XAD-7 resin was selected. Experiments prove that the best purification parameters of static adsorption and desorption were sample pH = 4.0 with 4 h of adsorption; and desorption solvent is 95% ethanol (pH = 7.0) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 31 publications
6
24
0
Order By: Relevance
“…On short, the ACs and antibacterial activities of the four extracts had the following order PRE-H > PRE ≈ URE-H > URE. The increases in the AC and antioxidant activity were related to the increases in the polyphenol levels that resulted from purification and HTHP, which was consistent with previous studies (Gao et al, 2018;Gornas et al, 2016;Xi et al, 2015).…”
Section: Changes In the Acs And Antibacterial Activities Of The Four supporting
confidence: 92%
See 1 more Smart Citation
“…On short, the ACs and antibacterial activities of the four extracts had the following order PRE-H > PRE ≈ URE-H > URE. The increases in the AC and antioxidant activity were related to the increases in the polyphenol levels that resulted from purification and HTHP, which was consistent with previous studies (Gao et al, 2018;Gornas et al, 2016;Xi et al, 2015).…”
Section: Changes In the Acs And Antibacterial Activities Of The Four supporting
confidence: 92%
“…The raw extracts always contain chlorophyll, proteins, polysaccharides, saponin and other impurities (Zhang et al, 2015a;Zhang et al, 2015b), which limit their applications. Macroporous resins, such as XDA-6 and AB-8, are weak polar resins that have been widely used in the separation and purification of plant polyphenols through electrostatic force, hydrogen bonding interactions, complexation and size sieving (Gao et al, 2018;Xi et al, Comparisons of the active components in four unripe raspberry extracts and their activites 2015). Here, four kinds of raspberry extracts were produced using different methods, as follows: 1) Unpurified raspberry extract (URE) was prepared from dried unripe raspberry powder by ultrasonic-assistant ethanol method; 2) URE-H was prepared from URE by HTHP; 3) purified raspberry extract (PRE) was prepared from URE by XDA-6 macroporous resin purification; and 4) PRE-H was prepared from PRE by HTHP.…”
Section: Introductionmentioning
confidence: 99%
“…Berries of Aronia melanocarpa are rich in valuable materials, exhibit a strong antioxidant activity and afford potential therapeutic benefits (hepatoprotective, gastroprotective, antiproliferative and anti-inflammatory activities) [ 9 , 10 , 25 , 26 , 27 ]. Among the activities, the antioxidant activity includes free radical scavenging, changes in effects of transition metals on oxidation, and inhibition of lipid peroxidation in several model systems, showing that AME is rich in bioactive polyphenols such as anthocyanins, flavanols, proanthocyanidins, and phenolic acids [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified the optimal parameters by RSM at the levels of 69% ethanol concentration (from the range of 60-80%) and 50 min sonication time (from the range of 40-60 min), which allowed 68.15 mg GAE/g of TPC to be extracted. In the study by Gao et al (2016), the optimal ethanol concentration for ultrasound extraction of phenolic compounds from chokeberry pulp was 56%. According to Chen et al (2018), the optimal ultrasound-assisted extraction conditions for determining TAC in chokeberries were: ethanol concentration 62% and ultrasonic time 44 min.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the extraction results for ethanol concentrations below the range analysed (60-96%) were clearly lower (by 15% for TPC, by 11% for DPPH and by 2% for TAC) than For the first time for chokeberry pomace, the response surface experiment of two factors (ethanol concentration and ultrasonic time) was carried out with TPC, TAC and DPPH as the response values. Gao et al (2016) and Chen et al (2018) used only one response value each -polyphenol and anthocyanin yield, respectively, whereas in RSM Xu et al (2017) applied total polyphenolic and flavonoids yields as the response values. What is more, in our experiment we used lyophilized pomace instead of whole frozen berries (Gao et al, 2016;Chen et al, 2018) or air-dried pomace (Xu et al, 2017) and it was performed at room temperature, and with a shorter extraction time, while the validation of the model obtained was performed with an error of less than 10%.…”
Section: Resultsmentioning
confidence: 99%